(untitled) (Journal of NELTA Gandaki, 2025)
This paper presents an analysis of how students use strategies for meaning construction through reading English texts. This narrative inquiry utilised in-depth interviews with four secondary-level students to explore their ways of learning English and constructing meaning from English texts. Findings show that students use their prior knowledge, collaborate with their friends, guess meaning from the context, seek the teacher’s support, visit libraries, and use dictionaries to comprehend the texts. This paper reports that struggling readers use limited strategies, such as using dictionaries and asking for support from their friends and teachers, whereas the engaged readers follow strategies such as grasping meaning from the context, using prior knowledge, getting support from others, and visiting libraries. The use of multiple strategies in meaning construction helps students better with library visiting and collaboration for better meaning construction. The findings imply that teachers’ support is necessary for students to develop their reading strategies.